INFLUENCE OF BANK CAPITAL EFFICIENT MANAGEMENT ON THE DEVELOPMENT OF INFRASTRUCTURAL MORTGAGES - Elena Posnaya; Aleksandr Kolesnikov; Yulia Antokhina (Вестник Северо-Кавказского федерального университета)
At present, a fairly relevant area of economic development is a state-private partnership for infrastructure development. Banking institutions in this matter occupy a leading position, since they are mediators in the implementation of infrastructure programs, fulfilling lending projects, focusing on the key rate of the Central Bank of the Russian Federation. Traditionally, in infrastructure projects a significant role - about 60 % of funding is played by banking institutions. Therefore, the key points in the study are to determine the significance of the infrastructure mortgage for business entities and the impact of effective bank capital management on the infrastructure mortgage. The government of the Russian Federation has the idea of an infrastructure developmentfund, which should become a central element of the infrastructure mortgage mechanism. In the event of a launch, the fund will allow launching a double lever mechanism - the project's co-financing function will be combined with raising funds through the issuance of fund bonds for state guarantees. Thus, the study examined the theoretical and practical signiicance of the infrastructure mortgage and bank capital management for the successful implementation of the infrastructure mortgage program in the Russian Federation.